Pengembangan Minat Siswa Kelas III SDN Jelupang 2 - Diah Ajeng Krianasari; Alya Salsabila (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
One of the phenomena in SDN JELUPANG 2, there are some third-grade students based hasiltest psikologin should students majoring in social studies by teachers enter incorporated into science stream. Some of these students by their teachers felt able to accept that there are lessons in class. However, the treatment teacher had an impact that is not good for their students. This study aimed to find out problems faced by students in majors that are not appropriate interest. This research uses descriptive method with qualitative approaches. Subjects were high school science students in grade III SDN JELUPANG 2. When research is done. From the results of this research is that students have problems at the majors that do not fit their interests, that students feel forced, pressured, bored in lessons given by teacher. And note also that students are also not eager to follow the lessons and not learning concentration.